New HOLIDAY Destination Decision Making; a Singapore perspective - Bhagchandani, Neeraj Vishindas (2015)
Singaporeans are known to have high disposable incomes and come from one of the more influential economies in Asia. Singaporeans have a sizeable impact on the world’s tourism industry. Thus, it is not surprising that they are the target of many tourism destination marketing organizations. Influencing this segment bears great international interest.